Soil energetics: A unifying framework to quantify soil functionality. Issue 4 (2nd November 2022) - Wacha, Kenneth; Philo, Allen; Hatfield, Jerry. L.
Abstract: Massive quantities of energy flow through soils during a year. Emerging views indicate that when supplied with abundant energy, soil biology acts as a self‐organizing system as soil microbes forge their habitats into a porous, well‐aggregated structure with high functionality. The flow of energy to power these self‐organizing processes has not been accounted for in present soil models, which concentrate on static pools of soil organic matter (SOM) and carbon and their relationship to soil functionality. To address this, we introduce a new conceptual energetics framework that quantifies the net energy flows within a soil control volume (CV) using a suite of energetic components including mechanical, biogeochemical, and hydrological processes. This framework is presented at a conceptual level and can be expanded to more granular levels with further study. To assess its present capabilities, management systems of conventional‐till (CT) and no‐till (NT) corn ( Zea mays L.)–soybean [ Glycine max (L.) Merr.] rotations and a grassland system (GS) were evaluated using the model. Net energy fluxes over a growing season were found to be negative for the CT, net zero for NT, and positive for GS. The energetics framework shows it can provide a first‐order assessment of soil health and advise which management practices provide adequate supplies of energy to soil biology to effectively enhance soil functionality. Core Ideas: Net positive supplies of energy support biological systems capable of altering the soil structure. Management practices impact energy fluxes through tillage type and intensity and raindrop‐induced erosion events. An energetic framework is proposed that is applied to three different management practices to assess energy balances. Seasonal net energy balances for conventional till, no till, and grassland system were negative, neutral, and positive, respectively.